Description Of An Animal Model Of Acute Cardiac Failure: In Vivo Experiments In Sheep - Cabrera Fischer, Edmundo Ignacio (2011)
The purposes of this work were to, a) describe an acute animal model of severe cardiac failure induced by high doses of halothane, b) ana- lyze the effects of these overdoses of halothane on ar- terial wall dynamics and c) characterize the cardi- ovascular effects of halothane through the autonomic nervous system. Measurements were performed in six sheep before and after halothane administration (4%). A significative decrease was observed in mean aortic flow (P<0.05) and diameter (P<0.01) in heart failure with respect to control state (from 2.64±0.95 L.min-1 and 17.32±1.86 mm to 1.69±0.58 L.min-1 and 15.33±1.71 mm; respectively). A significantly de- crease was observed in mean (P<0.005), systolic (P<0.01) and diastolic (P<0.005) aortic pressure in heart failure (from 85.90±19.49 mmHg, 93.52±18.07 mmHg and 78.86±20.12 mmHg to 49.12±21.77 mmHg, 55.54±20.71 mmHg and 43.48±21.21 mmHg; respectively). Heart rate in control group (127.73±11.20 bpm) was significantly (P<0.05) higher than that observed in heart failure (107.15±13.53 bpm).